Constraints to Optimal Implementation of Curriculum and Assessment Policy Statement (CAPS) in the North West Province in South Africa - Matsepe, David; Maluleke, Mugwena (African Journal of Peace and Conflict Studies, 2019)
Curriculum and Assessment Plan Statement in South Africa was introduced to develop, maintain and support a South African school education system. This curriculum policy was envisioned to give more detailed guidance on what teachers need to teach and how they should assess. However, Curriculum and Assessment Plan Statement appears not to be optimally implemented by rural public-school teachers. This study investigated the constraints faced by North West Province in the implementation of Curriculum and Assessment Plan Statement to suggest the intervention mechanisms to bring improvement in the rural public schools teaching and learning. This is in line with UNESCO's believe that any education system should strive to transform lives and build peace and security, eradicate poverty and drive sustainable development. Using the qualitative approach, data were collected through interviews and focus group discussions with grade 9 to 12 teachers from the secondary schools in the North-West Province, Zuluboy Moloto Region. The grounded (thematic) method was used to analyse the data. The findings revealed that the current state of the infrastructure, limited resources and limited teacher training fail to promote and support the implementation of Curriculum and Assessment Plan Statement. The study recommends that continuous CAPS training should be given to teachers on pedagogical knowledge and skills training related to specific subject matter disciplines.